(untitled) (Research, Society and Development, 2021)
There is a great difficulty in persons regarding their control of finances and making good use of Financial Planning in their Personal Finances. Taking it into account, we acknowledge the importance of this paper, which has as main objective to analyze whether academics of the Bachelor Degree of Accounting at the State University of Piauí, campus Picos, apply accounting techniques when planning their personal finances, as well as to identify the profile of socioeconomic status of the academics, establishing how they organize their personal finances and how they were financially educated, assessing whether there is a personal financial planning in order to improve the use of their income and, finally, to identify the importance of Accounting and the financial planning in the personal finances of these students. The methodology initially used in this work was bibliographic, through books and academic papers which dealt with the subject, secondly, a field research was carried out through a survey with objective questions about the theme. By using this research, the theoretical component and the analyzed responses of the survey, the paper’s objectives were fulfilled, concluding that the students present a good level of knowledge on the theme.